The Influence of Leadership Style and Rewards on Employee Performance with Self-Efficacy as a Mediation Variable in Pramita Manado Clinic Laboratory - Melinda Rambing Kong; Hery Winoto Tj; Fushen (PT FORMOSA CENDEKIA GLOBAL, 2023)
Changes in today's times that are getting faster bring company changes to be a challenge in itself. The company's success is inseparable from the importance of a leader in leading the company, besides that the awards given by the company will affect employee performance. The purpose of this study was to analyze the effect of leadership style and appreciation on employee performance with self-efficacy as a mediating variable at the Pramita Clinical Laboratory in Manado. The number of samples in this study were 80 respondents. The data used is a type of quantitative data obtained from filling out questionnaires by selected respondents through the total sampling method. The analytical method used in this research is through the Structural Equation Model (SEM) approach using the SmartPLS program. The results of this study indicate 1) leadership style has a positive and significant effect on self-efficacy, 2) rewards have a positive and significant effect on self-efficacy; 3) leadership style has no effect on employee performance; 4) rewards have no effect on employee performance; 5) self-efficacy has a positive and significant impact on employee performance; 6) leadership style influences employee performance through self-efficacy as a mediating variable; 7) rewards have an influence on employee performance through self-efficacy as a mediating variable at the Pramita Clinical Laboratory in Manado.